Beach hazard: rip current study and assessment of beach safety at selected recreational beaches along Pahang coastline - Muhammad Amirul Syafiq Hamsan
Rip current is defined as a wave-induced current starting at nearshore and flowing to an offshore direction. Rip current is a major global coastal hazard and is responsible for over 30 drowning cases along the Pahang coastline from 2006 to 2018. However, there are still no data available on rip current at the East Coast of Peninsular Malaysia. Thus, this research was carried out to classify the beach morphodynamics associated with rip current formation at selected beaches along Pahang coastline (Balok, Batu Hitam, Teluk Cempedak, Air Leleh, and Sepat). Before these beaches were selected, preliminary data collection was done along Pahang coastline from Chendor beach, (at northern of Pahang) to Hiburan beach, (at Kuala Rompin in the south). The justification for selecting these beaches were based on several criteria such as presence of public activity, presence of coastal guard tower, near to a hotel and/or residential area, and easy public access. There were four stages of this research which included 1) field sampling (samples collection) and beach profile survey. The output from this stage indicate the rip current probability at selected beaches; 2) Determination of rip current occurrence probability based on the grain size and beach profile data. Findings from this second stage showed that four out of five recreational beaches (Balok, Batu Hitam, Teluk Cempedak and Sepat) had high potential in developing rip current; 3) Determination of rip current occurrence and hazard at selected beaches during Southwest and Northeast monsoon. The results showed that Pahang coastline was categorized as rip-dominant intermediate beaches with several beaches were classified as barred (B), low tide terrace with rip (LTTR), and low tide bar and rip (LTBR). Beside, most of the beaches were exposed to different risk levels of rip current; high risk (Teluk Cempedak and Air Leleh beach), moderate risk (Balok and Batu Hitam beach), and mixed risk (Sepat beach); and last stage 4) Survey on public knowledge of beach safety and rip current hazard among beachgoers at Teluk Cempedak beach. The results indicated that most of the beachgoers had limited knowledge on beach safety and rip current hazard. This study would be useful to educate public on the rip current hazard which might cause drowning. Thus, this can reduce the drowning cases in Malaysia, particularly in Pahang.